Egrang Batok Traditional Game on Measurement Material - Pratama, Ridho Faisal Halim; Hidayati, Yulia Maftuhah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze the application of traditional egrang batok game as a learning media on measurement material in elementary school. Methodology: This study used a qualitative approach with subjects consisting of one mathematics teacher and 20 third grade students of SD Muhammadiyah Plus Malangjiwan Colomadu with the selection of interview subjects of one teacher and two students seen from the initial ability regarding measurement material. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. Data validity was obtained through triangulation of sources and techniques.Results: The results showed that the application of egrang batok game in measurement learning was associated with the practice of standard and non-standard units in measurement material. Students can understand the difference between standard and non-standard units through the activity of measuring step distance.Applications/Originality/Value: The novelty of the research lies in the use of the traditional game egrang batok as a learning medium.